Green Synthesis of Selenium Nanoparticles from Okra (Abelmoschus esculentus) Extract with Characterization and Antioxidant Activity - Susilo, Raden Joko Kuncoroningrat; Apsari, Retna; Hayaza, Suhailah; Cristian, Yeremia Budi; Prasetyo, Vania Griselda; Widianti, Imanda; Palmasih, Anastasia Alin; Jemon, Khairunadwa; Sajidah, Elma Sakinatus (Universitas Gadjah Mada, 2025)
Selenium nanoparticles (SeNPs) have gained attention in the medical field because of their enhanced bioactive properties and bioavailability. The green synthesis of nanoparticles offers an eco-friendly synthesis method. In this study, Abelmoschus esculentus (okra) extract was used for the green synthesis of SeNPs. The synthesized SeNPs were characterized using UV-visible (UV-vis), scanning electron microscopy-energy dispersive X-ray (SEM-EDX), Fourier-transform infrared spectroscopy (FTIR), and particle size analyzer (PSA). UV-vis analysis showed a peak at a wavelength of 288 nm, and the SeNPs demonstrated stability at low temperatures for up to 30 days. FTIR analysis indicated interactions between the pectin functional groups on okra and the surface of SeNPs. The SeNPs had a 6.48 nm diameter and polydispersity index of 0.13. A spherical morphology was observed in the nanoparticles. The antioxidant activity of SeNPs was evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) methods. The results showed a dose-dependent increase in free radical inhibition with 31.44 and 15.37% by DPPH and ABTS tests, respectively. The green synthesis of SeNPs using okra extract produced nanoparticles with unique properties based on several characterization results. In conclusion, SeNPs exhibited promising antioxidant activity, highlighting their potential for biomedical applications.